Diversidade e estrutura genética de Pilosocereus aureispinus: uma espécie de cactácea vulnerável e microendêmica - Ribeiro, Paulianny de Moura (Universidade Federal de São Carlos, 2015)
Pilosocereus aureispinus (Buining & Brederoo) F. Ritter is a narrow endemic columnar cactus of eastern Brazil, occurring at Ibotirama and Oliveira dos Brejinhos, Bahia. In this work the genetic diversity and population structure were assessed for eight microsatellite loci in four P. aureispinus localities of occurrence, covering its known distribution. Genetic diversity levels were relatively high (A = 4,2 e HE = 0,451) comparing with closely related species and other narrowly distributed plant species. Significant Hardy-Weinberg Equilibrium departures and linkage disequilibrium were not detected. Private alleles in low frequencies and low levels of genetic structure (FST =0,071 e G”ST = 0,132) were detected. STRUCTURE software analysis did not identified structure, showing that samples from four analyzed localities represent a unique genetic group (K=1). These results pointed to high level of ongoing gene flow among sampled localities, which may counteract differentiation effects and genetic diversity loss. Despite P. aureispinus is not suffering genetic variability erosion due its narrow distribution, the species should be classified as endangered (EN) at IUCN Red List of Threatened Species due existent anthropogenic disturbs in regions where it occurs.
Genetic diversity and population structure of Pilosocereus aureispinus: a vulnerable and microendemic cactus species
Keywords: Genética de populações; Population genetics; Cacto - genética; Cactus - genetics; Diversidade genética; Genetic diversity; CIENCIAS BIOLOGICAS::GENETICA::GENETICA VEGETAL